Natural Resources Management Literature 2000–2026 Identifying Research Fronts and Thematic Concentrations: A Bibliometric Study - Judijanto, Loso (West Science Nature and Technology, 2026)
This study aims to map the intellectual structure, thematic concentrations, and emerging research fronts in natural resources management (NRM) literature from 2000 to 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine co-occurrence networks, overlay visualization, and density patterns. The results indicate that NRM research has experienced significant growth, particularly in response to global challenges such as climate change, environmental degradation, and resource scarcity. Core themes remain centered on conservation, environmental protection, and ecosystem sustainability, reflecting the foundational orientation of the field. However, the findings also reveal a clear thematic shift toward more integrative and interdisciplinary approaches, including environmental monitoring, climate adaptation, and resource governance. Emerging research fronts are increasingly shaped by technological advancements, such as artificial intelligence, machine learning, and renewable energy, although these areas are still developing and less densely represented. Furthermore, the analysis highlights the dominance of certain regions in knowledge production while emphasizing the need for broader global participation. This study contributes to a deeper understanding of the evolution and current landscape of NRM research and provides valuable insights for future research directions, policy development, and sustainable resource management practices.